The influence of HRM practices on turnover among employees / Siti Najlaa Moh @ Mohd Sulaiman - Moh @ Mohd Sulaiman, Siti Najlaa (2012)
The purpose of this study is to assess the influence of HRM practices on turnover among employees. Given the uprising number of turnover among employees in the country which leads to 13 percent in 2010 and the negative side-effects of turnover towards organization, there may be a corresponding increase in the complaints about turnover effects filed by employers. Apart from that, there is a big chance that the number of inquiries from the employers in relation to influence of HRM practices on turnover among employees would also grow in accordance with increasing reports made by employers about the side-effects of turnover towards organization. In response to this possible national concern, a study was conducted recently to investigate the issue further. The purpose of the study described in this research report was to assess the current employers and employees' knowledge on the influence of HRM practices on turnover among employees. In the end of this study, it was found that there are other factors apart from HRM practices that should be taken into consideration in order to reduce turnover among employees. In addition, there are several strategies or practices that should be planned systematically in order to become employer of choice.